+0  
 
+1
216
4
avatar+1207 

If z^2 + z + 1 = 0, find \(z^{49} + z^{50} + z^{51} + z^{52} + z^{53}\).

 Apr 15, 2019
 #1
avatar+57 
+1

Hint:

 

You're trying to find \(z^{53}+z^{52}+z^{51}+z^{50}+z^{49}\), so factor out \(z^{49}\) to get \(z^{49}(z^4+z^3+z^2+z+1)\). We know what \(z^2+z+1\) is, so substitute it in. You now have\(z^{49}(z^4+z^3)\), which can be written as \(z^{51}(z^2+z)\). Now, we know that \(z^2 + z + 1=0\), so \(z^2+z=-1\). Substituting, we get \(-z^{51}\).

 

Continue from here.

 

-24

 Apr 15, 2019
edited by TwentyFour  Apr 15, 2019
edited by TwentyFour  Apr 15, 2019
 #2
avatar+106539 
+1

Very nice "24".....!!!!

 

 

cool cool cool

CPhill  Apr 15, 2019
 #3
avatar+23893 
+1

If

\(z^2 + z + 1 = 0\),

find \(z^{49} + z^{50} + z^{51} + z^{52} + z^{53}\).

 

\(\begin{array}{|rcll|} \hline \left(z^2 + z + 1 \right)^2 &=& 1+z^2+z^4+2z+2z^2 +2z^3 \\ \left(z^2 + z + 1 \right)^2 &=& 1+z^2+z^4+2z(z^2 + z + 1) \quad | \quad z^2 + z + 1 = 0 \\ \mathbf{0} &\mathbf{=} & \mathbf{1+z^2+z^4} \quad | \quad 0 = z^2 + z + 1 \\ z^2 + z + 1 & = & 1+z^2+z^4 \\ z & = & z^4 \quad | \quad : z \\ 1 & = & z^3 \\ \mathbf{z^3} &\mathbf{=} & \mathbf{1} \\ \hline \end{array} \)

 

\(\begin{array}{|lcll|} \hline z^4 = z^3z= 1\cdot z &=& z \\ z^5 = z^3z^2= 1\cdot z^2 &=& z^2 \\ z^6 = \left(z^3\right)^2= 1^2 &=& 1 \\ \hline \end{array}\)

 

In general:

\(\begin{array}{|lcll|} \hline z^{0+3n} = 1 \\ z^{1+3n} = z \\ z^{2+3n} = z^2 \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline z^{49} = z^{1+3\cdot16} &=& z \\ z^{50} = z^{2+3\cdot16} &=& z^2 \\ z^{51} = z^{0+3\cdot17} &=& 1 \\ z^{52} = z^{1+3\cdot17} &=& z \\ z^{53} = z^{2+3\cdot17} &=& z^2 \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline z^{49} + z^{50} + z^{51} + z^{52} + z^{53} &=& z+z^2+1+z+z^2 \quad | \quad z^2 + z + 1 = 0 \\ z^{49} + z^{50} + z^{51} + z^{52} + z^{53} &=& z+z^2 \quad | \quad z^2 + z = -1 \\ \mathbf{z^{49} + z^{50} + z^{51} + z^{52} + z^{53}} & \mathbf{=} & \mathbf{-1} \\ \hline \end{array}\)

 

laugh

 Apr 16, 2019
 #4
avatar+7763 
0

\(z^2+z+1 = 0\\ (z-1)(z^2+z+1)=0\\ z^3 = 1, z \neq 1\\ z = -\dfrac{1}{2} + \dfrac{i\sqrt3}{2}\\ z^2 = -\dfrac{1}{2} - \dfrac{i\sqrt3}{2}\\\)

 

 

\(z^{49} + z^{50} + z^{51} + z^{52} + z^{53}\\ =z + z^2 + 1 + z + z^2\\ =1+2(-\dfrac{1}{2} + \dfrac{i\sqrt3}{2} + -\dfrac{1}{2} - \dfrac{i\sqrt3}{2})\\ =1 + 2(-1)\\ = -1\)

.
 Apr 18, 2019

21 Online Users

avatar
avatar